2018
DOI: 10.5897/ijeaps2018.0568
|View full text |Cite
|
Sign up to set email alerts
|

Effect and snags of provision of in-service education and training for teachers in basic schools for the deaf

Abstract: Regular and effective provision of in-service training for teachers is a necessary practice for the educational development of any country. The provision of effective in-service training and education for special teachers is however bedeviled with many challenges. To appraise the effect and problems of inservice training in Ghana, a survey involving 90 teachers from three schools for the deaf namely: Savelugu, Wa and Gbeogo Schools for the Deaf were sampled in this study. A set of 94 questionnaire and 4 exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Komba and Mwakabenga (2019) also point out that teachers learnt from the training content that was not related to their context of work. Similarly, Issaka (2018) found that the INSET training programmes were ineffective among teachers because of the discrepancy between teachers' needs and what the training provided. In addition, Tuncel and Cobanoglu (2018) found that INSET did not significantly contribute to teachers' professional development.…”
Section: Discussionmentioning
confidence: 99%
“…Komba and Mwakabenga (2019) also point out that teachers learnt from the training content that was not related to their context of work. Similarly, Issaka (2018) found that the INSET training programmes were ineffective among teachers because of the discrepancy between teachers' needs and what the training provided. In addition, Tuncel and Cobanoglu (2018) found that INSET did not significantly contribute to teachers' professional development.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling technique used was random sampling. We determined the number of samples in this study using the formula recommended by Cecilia (2018), which resulted in 100 high school teachers. A total of three schools in East Jakarta were selected as an affordable population -these three represent the larger and most outstanding schools of the total schools.…”
Section: Participantsmentioning
confidence: 99%
“…To this end, Edem et al (2020) noted that, though the adopting and integrating ICT in Ghanaian schools have been generally slow, the rate of adoption and integration has even been slower in schools for children with disabilities. For example, Alimatu Issaka (2018) observed that acquisition of competent ICT teaching staff as well as the ICT for facilitating the learning of other subjects is a major challenge in most of the schools for deaf in Ghana. The application of ICT into classroom instructional activities has recently gained much attention in the public discourse, particularly among developing countries (Moreira et al,2019).…”
Section: Introductionmentioning
confidence: 99%